STUDI SURVEI KEMAMPUAN TOLAKAN PELURU PADA SISWA JENJANG PENDIDIKAN SMP - Falahah, Nurul; Handayani, Heni Yuli; Widodo, Haryo Mukti; Purwoto, Septyaningrum Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research started from the author's observation, namely that there was no data on the shot put ability of new class VII students, so this research wanted to find out about a survey study of the shot put ability of NU Arosbaya Middle School students. The type of research used in this research is survey research. The sample in this research was 20 class VII students at NU Arosbaya Middle School. The results of the research showed that there were 0 students who had repulsion abilities in the very good category with a percentage of 0%, the good category had 1 person with a percentage of 25%, the adequate category had 5 people with a percentage of 25%, the poor category had 14 people with a percentage of 70%, and the very poor category with a percentage of 0%. The conclusion of this research is that the shot put ability of NU Arosbaya Middle School students is in the poor category. Therefore, the recommendation given is that it is necessary to carry out classroom action research or experiments by providing training or learning methods to improve students' rejection abilities.